2021
DOI: 10.3389/fpls.2021.666796
|View full text |Cite
|
Sign up to set email alerts
|

QTL for Main Stem Node Number and Its Response to Plant Densities in 144 Soybean FW-RILs

Abstract: Although the main stem node number of soybean [Glycine max (L.) Merr. ] is an important yield-related trait, there have been limited studies on the effect of plant density on the identification of quantitative trait loci (QTL) for main stem node number (MSNN). To address this issue, here, 144 four-way recombinant inbred lines (FW-RILs) derived from Kenfeng 14, Kenfeng 15, Heinong 48, and Kenfeng 19 were used to identify QTL for MSNN with densities of 2.2 × 105 (D1) and 3 × 105 (D2) plants/ha in five environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
(79 reference statements)
1
0
0
Order By: Relevance
“…The number of stem node in the Grobogan variety decreased with increasing irradiation dose, resulting in a decrease in the number of leaves and branches. This is consistent with studies that have identified main stem node number as an important yield-related trait in soybeans, with variations observed across different plant densities and environments [17].…”
Section: Vegetative Characteristics Of M1 Soybean Mutants In Field Ex...supporting
confidence: 92%
“…The number of stem node in the Grobogan variety decreased with increasing irradiation dose, resulting in a decrease in the number of leaves and branches. This is consistent with studies that have identified main stem node number as an important yield-related trait in soybeans, with variations observed across different plant densities and environments [17].…”
Section: Vegetative Characteristics Of M1 Soybean Mutants In Field Ex...supporting
confidence: 92%